Self concepts of elementary school principals in the Division of Isabela in relation to their role behavior - Rabot, Natividad B. 1918- (s.n.], 1969)
The study aims to investigate the self concept and role behavior of a sample of 33 public elementary school principals in the division of Isabela, and to explore the relationships that may exist between these two variables. Using two instruments, the Index of Adjustment and Values and the Leader Behavior Description Questionnaire Form XII, the description of self concept on four interpretative levels and the descriptions of role behavior from the subject, the classroom teachers and the supervisors are secured.